2017
DOI: 10.1093/cid/cix1076
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance and the Risk of Recurrent Bacteremia

Abstract: Antibiotic nonsusceptibility was consistently associated with higher risks of recurrent bacteremia, but the estimated number of additional recurrent episodes in the Netherlands (40 per year) was rather limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…This is noteworthy as extended-spectrum cephalosporin resistance increased in U.S. hospitals from 5.46% to 12.97% between 2009 and 2016 ( 28 ). In addition, a recent Dutch study found that resistance to third-generation cephalosporins in Enterobacteriaceae is a significant risk factor for recurrence in bloodstream infections ( 29 ). The shared relative prevalence of the 12 most common O-antigen serotypes between BSI and UTI strains is consistent with the association between strains responsible for sepsis and strains sourced from urinary tract infections ( 30 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is noteworthy as extended-spectrum cephalosporin resistance increased in U.S. hospitals from 5.46% to 12.97% between 2009 and 2016 ( 28 ). In addition, a recent Dutch study found that resistance to third-generation cephalosporins in Enterobacteriaceae is a significant risk factor for recurrence in bloodstream infections ( 29 ). The shared relative prevalence of the 12 most common O-antigen serotypes between BSI and UTI strains is consistent with the association between strains responsible for sepsis and strains sourced from urinary tract infections ( 30 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, only one of them included a limited number of cases of bloodstream infections produced by P . aeruginosa (BSI-PA), and thus the question on the efficacy of short treatments remains open for this microorganism, whose ability to produce relapsing infections and breakthrough antibiotic resistance is superior to other Gram-negative bacteria [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, three randomized trials have confirmed the non-inferiority of 7-day courses of antibiotics compared to 14-day schemes for non-complicated bacteremic infections produced by Gram-negative bacilli [9][10][11]. Nevertheless, only one of them included a limited number of cases of bloodstream infections produced by P. aeruginosa (BSI-PA), and thus the question on the efficacy of short treatments remains open for this microorganism, whose ability to produce relapsing infections and breakthrough antibiotic resistance is superior to other Gram-negative bacteria [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of pathogenic bacteria to survive therapeutic intervention is quickly becoming a major medical crisis of the modern world, where the emergence of multidrug resistance amongst Gram-positive and -negative bacteria have rendered conventional antimicrobials inept (Frieri et al 2017). Several resistance mechanisms have been recognised within bacterial populations including immunosuppression of the host, evasion of immune response by the pathogen and ineffectiveness of antibiotic therapies (Woudt et al 2018). Persister cells are a survival mechanism exhibited by bacteria, during the exponential growth phase, in response to a range of adverse environmental conditions (Fisher et al 2017).…”
Section: Introductionmentioning
confidence: 99%